Pendampingan Lembaga Pendidikan Formal Untuk Pemilih Pemula di SMA Al Anwari Tanah Merah Kabupaten Bangkalan - Muni, Abd; Amalia, Jihan; Fakhruzy, Agung; Nafilah, Ummi (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: Political participation in a democratic country is an indicator of the implementation of the highest legitimacy of state power by the people (popular sovereignty). The higher the level of political participation, the more visible it is that people follow, understand and participate in state activities. The role of first-time voters in casting their vote is very important for a better democratic process.Purposes of Devotion: This assistance is carried out to support first-time voters in understanding and exercising their electoral rights. This program aims to provide in-depth knowledge about the election process, rights and obligations as voters, as well as the importance of involvement in democracy. Method of Devotion: The implementation method for this Community Service (PKM) activity uses the PAR (Participatory Action Research) method. This service activity is carried out in several stages of implementation activities as follows: Lecture and Question and Answer, discussion and evaluation.Results of the Devotion: With this assistance, there is an increase in interest and motivation among students who take part in the assistance to participate in general elections and other political activities as part of Indonesian citizens. The level of satisfaction of the majority of students who take part in this mentoring activity is higher and creates a sense of self-confidence and readiness to use their voting rights wisely according to their own conscience and choices.